Measuring Unbound Versus Total Piperacillin Concentrations in Plasma of Critically Ill Patients: Methodological Issues and Relevance. Issue 3 (June 2019) - Colman, Sofie; Stove, Veronique; De Waele, Jan J.; Verstraete, Alain G.
Abstract : Background: Piperacillin is considered a moderately protein-bound antibiotic (20%–40%), with albumin being an important binding protein. Although infrequently used in practice, different methods to measure the fraction unbound (fu) are available, but uncertainty remains as to what the most appropriate method is. The main goal of this study was to estimate the impact of the methodology used to measure unbound piperacillin in plasma on the fu of piperacillin; we compared ultrafiltration (UF) at 4°C and 37°C with the reference method, equilibrium dialysis. In addition, we analyzed the impact of other proteins on the fu. Methods: Anonymized left-over Li-heparin plasma samples (n = 41) from 30 critically ill patients who were treated with piperacillin were used for the analyses. Results: We found that the piperacillin fu, determined by UF, is on average 8% higher at 37°C (91%) than at 4°C (83%). There were no systematic or proportional differences between UF at 4°C and equilibrium dialysis at 4°C. This emphasizes the importance of the temperature during UF, which should therefore be clearly stated in publications that report on the methodology of UF. No significant impact of the albumin-, IgA-, total protein-, or α1-acid glycoprotein concentration on the fu was found. The fu found in this study was higher than the generally assumed fu value of 60%–80%. A possible explanation lies in the studied population or in the temperature used. Based on our results, routine monitoring of unbound piperacillin in intensive care unit patients is not recommended. Conclusions: Based on the prediction model, we can state that in intensive care patients the fu of piperacillin is 91% (SD 7%), determined with UF at 37°C.